Effect of visual stimuli on the jumping ability of amateur soccer players - Mateos, G.; Sillero-Quintana, M.; Balsalobre-Fernández, C. (Journal of Human Sport & Exercise, 2023)
In soccer, high levels of strength applied in short durations are crucial for various performance-related actions such as accelerations, decelerations, sprints, jumps, and changes of direction. These actions often occur in the presence of visual stimuli that require attention and rapid reaction. Recent training methodologies propose integrating visual stimuli to enhance sport-specific physical abilities. However, limited research has investigated the impact of visual stimuli on explosive force production abilities. Therefore, this study aimed to analyse the influence of reacting to non-specific visual stimuli on seated and counter-movement vertical jump performance. Seventeen senior amateur soccer players (age: 22.9 ± 2.8 years; height: 172.0 ± 8.5 cm; weight: 71.1 ± 7.3 kg) were recruited as participants for this study. Participants performed seated vertical jumps (SJsit-90º) and counter-movement vertical jumps (CMJ) under two conditions: with reaction to a visual stimulus (REAC) and without reaction (VOL). The order of the conditions was counterbalanced across participants. The statistical analysis revealed a significant decrease in the height of SJsit-90º in the REAC condition compared to the VOL condition (HeightVOL-REAC = 1.88 ± 2.16 cm; p < .001). Although a similar trend was observed, no significant differences were found in CMJ height between conditions (HeightVOL-REAC = 0.70 ± 0.63 cm; p = .277). It is concluded that the inclusion of non-specific visual stimuli to react to significantly and negatively affects the ability to apply force measured through seated vertical jumps. These findings emphasize the importance of considering the potential detrimental effects of external visual stimuli on explosive force production when designing training protocols for soccer players.